2015
DOI: 10.3109/01902148.2015.1060275
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor restores surfactant protein-C expression in alveolar-epithelial type II cells and attenuates bleomycin-induced pulmonary fibrosisin vivo

Abstract: Decreased expression of SFTPC by TGF-β1 treatment was restored by TSA via hyperacetylation of histone H4 in the promoter region. TSA partially attenuated pulmonary fibrosis and increased Sftpc mRNA in ATII. Our findings suggest that the epigenetic restoration of SP-C would be a therapeutic target for pulmonary fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…Epigenetic mechanisms are well known to play a key role in fibrosis (Helling and Yang, 2015;Page and Mann, 2015;Yang and Schwartz, 2015). Specifically in pulmonary fibrosis and fibroblast biology, changes in DNA methylation (Huang et al, 2014;Qu et al, 2018;Sanders et al, 2012;Yang et al, 2014), microRNAs (Khalil et al, 2015;Liu et al, 2010;Miao et al, 2018;Yang et al, 2013) and histone-modifying enzymes (Bai et al, 2019;Bombardo et al, 2018;Conforti et al, 2017;Coward et al, 2014Coward et al, , 2009Glenisson et al, 2007;Hemmatazad et al, 2009;Khalil et al, 2015;Korfei et al, 2015;Ota et al, 2015;Sanders et al, 2014Sanders et al, , 2017 have been shown to accompany and drive lung fibroblast activation and disease progression. Our screen interrogated the effects of a multitude of epigenetic-modifying small molecules, and identified effects of a variety of epigenetic writers, erasers and readers, demonstrating the complexity and importance of epigenetic regulators in controlling fibroblast biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic mechanisms are well known to play a key role in fibrosis (Helling and Yang, 2015;Page and Mann, 2015;Yang and Schwartz, 2015). Specifically in pulmonary fibrosis and fibroblast biology, changes in DNA methylation (Huang et al, 2014;Qu et al, 2018;Sanders et al, 2012;Yang et al, 2014), microRNAs (Khalil et al, 2015;Liu et al, 2010;Miao et al, 2018;Yang et al, 2013) and histone-modifying enzymes (Bai et al, 2019;Bombardo et al, 2018;Conforti et al, 2017;Coward et al, 2014Coward et al, , 2009Glenisson et al, 2007;Hemmatazad et al, 2009;Khalil et al, 2015;Korfei et al, 2015;Ota et al, 2015;Sanders et al, 2014Sanders et al, , 2017 have been shown to accompany and drive lung fibroblast activation and disease progression. Our screen interrogated the effects of a multitude of epigenetic-modifying small molecules, and identified effects of a variety of epigenetic writers, erasers and readers, demonstrating the complexity and importance of epigenetic regulators in controlling fibroblast biology.…”
Section: Discussionmentioning
confidence: 99%
“…BRD4) (Tang et al, 2013) and EZH2 (Coward et al, 2018;Xiao et al, 2016) were identified. We chose to focus on pracinostat because it was most effective in our primary assay outcome, and because HDAC inhibition has proven effective in fibrosis models (Barter et al, 2010;Bombardo et al, 2018;Conforti et al, 2017;Glenisson et al, 2007;Guo et al, 2009;Kang et al, 2017;Khalil et al, 2015;Kim et al, 2018;Ota et al, 2015) but its anti-fibrotic effects remain poorly understood. However, we also note that inhibitors of several enzymes not previously linked to fibrosis were identified in our screen, such as L3MBTL3, a reader of methylated-lysine on histones (Min et al, 2007;Trojer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Early Transcriptional Changes in Arl13b flox/flox ; Ksp-Cre Mice Because HDACIs have been shown to suppress fibrosis, including renal fibrosis, [27][28][29][30][31][32][33][34][35][36][37] we investigated the effect of VPA treatment on fibrosis in Arl13b flox/flox ; Ksp-Cre mice. VPA treatment from P10 to P25 significantly reduced collagen deposition in mutant mice as shown by trichrome staining ( Figure 5G).…”
Section: Vpa Treatment Ameliorates Fibrosis and Suppressesmentioning
confidence: 99%
“…This response, termed mitohormesis, is being rapidly dissected in many model systems and must be considered in the design of all mitochondrial-targeted therapeutics for the treatment of lung disease (66). Other mitochondrial-targeted therapeutic strategies that could potentially be used to treat lung diseases include the use of metabolic modulating compounds such as dicholoroacetate (138), histone deacetylase inhibitors (139,140), and fission inhibitors. Stimulating adaptive mitochondrial biogenesis and mitophagy may be a useful adjuvant therapy for ALI in sepsis (44), and transfer of mitochondria from bone marrowderived mesenchymal stem cells to injured alveolar epithelium may be beneficial in ARDS, asthma, or COPD (141).…”
Section: Mtdampsmentioning
confidence: 99%